ONLINE DISPUTE RESOLUTION IN BRAZIL: ARE WE READY FOR THIS CULTURAL TURN? (Revista Paradigma, 2016)
Litigiousness is a social phenomenon.The complaints that Brazilian´s court are now running are very inflated.Judges are burdened.With this in mind, it is important to say that there is a promising future for digital economy.Online dispute resolution (ODR) is a new method for addressing disputes that arose online.The growth of onlinedispute resolution is tied to the growth of e-commerce.Given the background, we think that it is a mistake to believe that Online Dispute resolution and Alternative Dispute Resolution (ADR) will ever replace any sizable proportion of our litigation in Court, but it is important to increase and improve more pacific and less costly means of dispute resolution in Brazil. ODR is a new form of dispute resolution in comparison to conventional courtrooms and even to ADR mechanisms. These methods are able to deliver justice in a digital society.